2018
DOI: 10.21726/abc.v5i2.595
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the size and degree of conservation of remnants of the Atlantic rain forest on chiropteran assemblages

Abstract: Reduction in the size and loss of the quality of habitats are considered the greatest threats to bat species. Aiming to complement information, the objective of this study was to evaluate, from compiled data, the influence of the size of forest fragments and their degree of conservation on the richness and composition of chiropteran fauna in the Atlantic rain forest. A total of 33 publications on Chiroptera in the Atlanticrain forest was reviewed and a list of 86 species was extracted from them. The size of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In the present study, we observed higher abundance of S. lillium compared to S. tildae (Table 1), a pattern that is maintained throughout the Atlantic Forest (Faria 2006, Faria & Baumgarten 2007, Brito 2011, Carvalho et al 2013, Luz et al 2013, Pires & Cademartori 2018. In the Atlantic Forest of Northeast Brazil (present study, Faria 2006, Faria & Baumgarten 2007 the abundance of S. lillium is lower than in the southern portion of this biome (Passos et al 2003, Esbérard et al 2006, Brito 2011, Carvalho et al 2013, Luz et al 2013, Souza et al 2015).…”
Section: Sturnira Tildaesupporting
confidence: 61%
“…In the present study, we observed higher abundance of S. lillium compared to S. tildae (Table 1), a pattern that is maintained throughout the Atlantic Forest (Faria 2006, Faria & Baumgarten 2007, Brito 2011, Carvalho et al 2013, Luz et al 2013, Pires & Cademartori 2018. In the Atlantic Forest of Northeast Brazil (present study, Faria 2006, Faria & Baumgarten 2007 the abundance of S. lillium is lower than in the southern portion of this biome (Passos et al 2003, Esbérard et al 2006, Brito 2011, Carvalho et al 2013, Luz et al 2013, Souza et al 2015).…”
Section: Sturnira Tildaesupporting
confidence: 61%
“…Historically, bats were sampled in this area only in the vicinity of the zoo. As T. nicefori is considered to be a rare specialist species in the Atlantic Forest domain (Pires and Cadermatori 2018), the record from the PEDI indicates that a comprehensive sampling effort can guarantee a more definitive inventory of the bat diversity of an area, even in highly impacted urban forest fragments. within the scope of this research program.…”
Section: Discussionmentioning
confidence: 99%